Improving Socially Sustainable Design and Construction in Developing Countries. (2016) - Pocock, James; Steckler, Carey; Hanzalova, Barbora
Abstract: Many construction projects in developing countries are unsustainable. Whether built by multi-national companies, non-government organizations (NGO's) or a deployed military force, projects are too often beyond the capabilities of local populations to build, operate, maintain or even relate to culturally. This paper examines definitions of sustainability, sustainability rating systems, lessons learned from unsustainable projects and sustainable construction research. Projects are often unsustainable in the developing world because the social aspect of sustainability is not fully considered. The authors examine case studies from a variety of organizations to illustrate best practices in socially sustainable projects. This paper considers how architects, engineers, builders, owners and communities in developing countries can best apply social sustainability to find appropriate design and construction solutions that maximize life-cycle project success. To that end, the authors recommend applying these social sustainability processes to projects in the developing world: 1. Secure land in a way that is legal and sensitive to local culture 2. Engage the community in the entire life cycle of the project 3. Design with sensitivity to the local culture 4. Design for maximum efficiency of limited water supplies 5. Design locally sustainable systems for energy and thermal comfort 6. Design for the safety of the occupants by incorporating local codes while acknowledging international standards 7. Design projects that can be safely constructed by the local population (given training opportunities) 8. Build using locally understood construction methods 9. Build with locally sustainable and affordable materials